A new species of Scinax Wagler (Anura: Hylidae) from Paraná, Southern Brazil - Conte, Carlos E.; Araujo-Vieira, Katyuscia; Crivellari, Lucas B.; Berneck, Bianca V. M. (Zootaxa, 2016)
In this article, we describe a new species of Scinax from the state of Paraná, southern Brazil, based on the external morphology of adults and their advertisement calls. The new species is diagnosed by the size of its males (SVL 27.8–31.6 mm); the snout subovoid in the dorsal view and slightly acuminate in profile; the vocal sac subgular and ventrally not reaching the pectoral region; and the advertisement call composed of a single pulsed note with 7–13 pulses, and a duration of 0.16–0.25s. This new species occurs in natural highland grassland formations, in the threatened ecosystem of the Atlantic Forest in the state of Paraná, southern Brazil.